2021
DOI: 10.3390/ijms22158036
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gut Microbiota in Overcoming Resistance to Checkpoint Inhibitors in Cancer Patients: Mechanisms and Challenges

Abstract: The introduction of immune checkpoint inhibitors has constituted a major revolution in the treatment of patients with cancer. In contrast with the traditional cytotoxic therapies that directly kill tumor cells, this treatment modality enhances the ability of the host’s immune system to recognize and target cancerous cells. While immune checkpoint inhibitors have been effective across multiple cancer types, overcoming resistance remains a key area of ongoing research. The gut microbiota and its role in cancer i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 147 publications
(281 reference statements)
0
21
0
Order By: Relevance
“…Microbial metabolites are also known to regulate the immune response to cancer. Butyrate was one of the first bacterial products implicated in cancer progression and response to immune therapy ( 66 ). Novel metabolites and mechanisms of action have been recently described.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial metabolites are also known to regulate the immune response to cancer. Butyrate was one of the first bacterial products implicated in cancer progression and response to immune therapy ( 66 ). Novel metabolites and mechanisms of action have been recently described.…”
Section: Discussionmentioning
confidence: 99%
“…This result has distinct proteomic and metabolomic signatures and confirmed that the gut microbiome regulates these changes. [11] The restoration of the microbiome ecosystem might improve the symptoms of steroid-refractory patients. Therefore, to improve the steroid-refractory state, stool from a healthy male was transplanted.…”
Section: Discussionmentioning
confidence: 99%
“…This became relevant when some favorable bacteria were found to be associated with decreased peripheral Treg levels, thereby halting the suppression of the lymphocyte. These low levels of Treg seemed to correlate with good response to immunotherapy, further drawing an association between bacteria and response to treatment [ 85 ]. The communication between gut microbiota and immunological response could possibly be mediated by products of bacteria metabolism [ 85 ].…”
Section: Novel Therapeutic Approaches In Management Of Urological Dis...mentioning
confidence: 99%